BENTUK KEKERASAN PADA PEREMPUAN DALAM HUBUNGAN BERPACARAN DI FILM - Catur Priyadi; Rafika Rani (Jurnal Pustaka Komunikasi, 2020)
Film is an effective mass communication media in conveying various kinds of messages. From the aspect of communication, films have many advantages compared to other media because they are presented in an audio-visual form. Possessive films are interesting to study because they highlight forms of dating violence that are still underestimated and different from other teen films that have been circulating in the market. Researchers conducted in-depth research and found dating violence was in the first position. This study wanted to reveal the form of violence against women in dating in possessive films. The theory used to support this research is Charles Sanders Peirce's Semiotic Analysis to analyze the meaning of signs, objects, and interpretants in each scene of violence that is displayed. This research uses descriptive analysis with a qualitative approach and uses a critical paradigm. Data collection techniques using documentation study and literature study and supported by triangulation. The results of the analysis in possessive films show that there are forms of violence against women in dating as well as gender bias which has always characterized women as weak and dependent on men until now.